2016
DOI: 10.1159/000443835
|View full text |Cite
|
Sign up to set email alerts
|

The Monocyte-to-Lymphocyte Ratio Correlates with Psycho-Neuro-Inflammatory Factors in Patients with Stable Coronary Artery Disease

Abstract: Background: Psychosocial stress and depression have been recognized as major risk factors of coronary artery disease (CAD). Although monocytes are known to be key players in atherosclerosis, monocyte-based associations with psychoneuroendocrino-immuno-inflammatory (PNI) markers have not been widely investigated in stable CAD. Objective: We examined associations between the monocyte-to-lymphocyte ratio (MLR) and key PNI markers in stable CAD. Methods: We studied 23 patients with stable CAD who completed the Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…It was reported that a higher MLR was correlated with increased susceptibility to clinical malaria and low malaria vaccine efficacy, implying increased MLR was also related to impaired immune responses. Recently, one study indicated that elevated MLR was associated with depressive symptoms and increased psycho‐neuro‐inflammatory markers in stable coronary artery disease . Two studies compared MLR and NLR in certain clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that a higher MLR was correlated with increased susceptibility to clinical malaria and low malaria vaccine efficacy, implying increased MLR was also related to impaired immune responses. Recently, one study indicated that elevated MLR was associated with depressive symptoms and increased psycho‐neuro‐inflammatory markers in stable coronary artery disease . Two studies compared MLR and NLR in certain clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one study indicated that elevated MLR was associated with depressive symptoms and increased psycho-neuro-inflammatory markers in stable coronary artery disease. 35 Two studies compared MLR and NLR in certain clinical settings. One signified that MLR was better than NLR in measuring systemic inflammatory responses in clear cell renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid cells (i.e. monocytes) have been associated both with inflammation (Gordon & Taylor, 2005; Robbins & Swirski, 2010) and several forms of psychosocial stress including low social economic status (Powell et al, 2013), perceived social isolation (Cole et al, 2015), and depressive symptoms in patients with coronary artery disease (Serfozo et al, 2016). In addition, secondary lymphoid tissue is an important initiator of the immune response, contains a high density of functional B cells (von Andrian & Mempel, 2003), and is an area of rapid turnover of B cells (Thomas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, in patients with coronary artery disease M/L ratio was evaluated and it was concluded that increased M/L ratio was associated with increase in depressive symptoms. In the same Preoperative levels of inflammatory biomarkers in patients with bilateral inferior turbinate hypertrophy study, increase in M/L ratio was demonstrated to be directly proportional to increase in neuroendocrine-sympathetic activity, onset, and progression of atherosclerosis, and the authors concluded that M/L ratio can be used as an inflammatory marker in the follow-up of the patients [15]. In our study we couldn't find a statistically significant difference between both groups as for N/WBC ratio.…”
Section: Discussionmentioning
confidence: 92%